1999
DOI: 10.2307/2640830
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection on Thermogenic Capacity of High-Altitude Deer Mice

Abstract: Adaptive explanations that rely on physiological arguments are common, but tests of hypotheses about the significance of whole-animal physiological performance (e.g., aerobic capacities) are rare. We studied phenotypic selection on the thermogenic capacity (i.e., maximal rate of oxygen consumption [V0 2 max] elicited via cold exposure) of high-altitude (-3800 m) deer mice (Peromyscus maniculatus). A high V0 2 max equates to a high capacity for heat production and should favor survival in the cold environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
186
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(203 citation statements)
references
References 46 publications
(60 reference statements)
14
186
1
Order By: Relevance
“…These tradeoffs in O 2 -transport efficiency at different O 2 partial pressures (PO 2 's) suggest that the highaffinity ␣-globin genotype may confer highest fitness in highaltitude environments, whereas the low-affinity genotype may confer highest fitness in low-altitude environments (10)(11)(12)(13)(14). Consistent with this hypothesis, survivorship studies of freeranging deer mice demonstrated that aerobic performance is subject to strong directional selection at high-altitude (15) and electrophoretic surveys of ␣-globin polymorphism in deer mice from western North America revealed striking altitudinal patterns of allele frequency variation that are consistent with the predicted rank-order of genotypic fitnesses across environments: The high-affinity ␣-globin electromorph is present at high frequency in high-altitude populations (Ͼ2,750 m), whereas the low-affinity electromorph is either fixed or nearly fixed in low-altitude populations [Ͻ1,750 m; (16)]. Moreover, patterns of nucleotide diversity and linkage disequilibrium (LD) at the two HBA paralogs are indicative of spatially varying selection between high-and low-altitude populations (17,18).…”
supporting
confidence: 50%
“…These tradeoffs in O 2 -transport efficiency at different O 2 partial pressures (PO 2 's) suggest that the highaffinity ␣-globin genotype may confer highest fitness in highaltitude environments, whereas the low-affinity genotype may confer highest fitness in low-altitude environments (10)(11)(12)(13)(14). Consistent with this hypothesis, survivorship studies of freeranging deer mice demonstrated that aerobic performance is subject to strong directional selection at high-altitude (15) and electrophoretic surveys of ␣-globin polymorphism in deer mice from western North America revealed striking altitudinal patterns of allele frequency variation that are consistent with the predicted rank-order of genotypic fitnesses across environments: The high-affinity ␣-globin electromorph is present at high frequency in high-altitude populations (Ͼ2,750 m), whereas the low-affinity electromorph is either fixed or nearly fixed in low-altitude populations [Ͻ1,750 m; (16)]. Moreover, patterns of nucleotide diversity and linkage disequilibrium (LD) at the two HBA paralogs are indicative of spatially varying selection between high-and low-altitude populations (17,18).…”
supporting
confidence: 50%
“…Its central importance is reflected in the thousands of studies published on energy metabolism (Houston et al, 1993;Hayes and O'Connor, 1999;Speakman, 2008; Burton et al, 2011, Konarzewski andKsiążek, 2013;White and Kearney, 2013). Despite these studies, many questions about metabolic rates and energy metabolism remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary observational study of a population of contemporary hunter-gatherers (the Ache of eastern Paraguay), Kaplan and Hill (1985) found that, among males, hunting ability (presumed to be a composite of skill and the ability to pursue prey) was associated with increased reproductive success, defined as survivorship of offspring. Additional support comes from animal research (Hayes & O'Connor, 1999;Jayne & Bennett, 1990). Studies show that the amount of time a constant speed can be sustained (i.e.…”
Section: Domain Of ''Moderate'' Intensitymentioning
confidence: 99%